Springboard (Nigeria) helps youth enter farming - Afere, Lawrence (Technical Centre for Agricultural and Rural Cooperation, 2018)
Lawrence Afere, Founder and CEO of Springboard Entrepreneurship Development Initiative (Nigeria) shares how he has been engaging youth into farming for job creation.